Teachers' Readiness Indicators on ICT Integration into their Teaching - Rea Aisha Champa; Dewi Rochsantiningsih; Diah Kristiana (BIRCU, 2019)
By the rapid change in innovations of Information and Communication Technology, people are now able to get and exchange information fast. To keep up with these innovations, the integration of ICT in education is urgently demanded of time at present as ICT is being used in almost all other sectors all over the world. Therefore, it demands the teachers to be skillful in operating ICT during their teaching. Nevertheless, the integration of ICT into teaching in Indonesia hasn’t fully been maximized. This paper is intended to investigate the factors of teachers’ readiness to integrate ICT into their teaching. To acquire an in-depth result, this case study focuses on the interview of some teachers in a certain school in Indonesia. The data gained revealed four factors that enact the integration of ICT in class. Most of the teachers need official trainingconcerning the integration of recent ICTs in class to optimize their teaching skills using ICT.